2013
DOI: 10.2139/ssrn.2338504
|View full text |Cite
|
Sign up to set email alerts
|

Growth Beyond Imbalances. Sustainable Growth Rates and Output Gap Reassessment

Abstract: The Great Recession' was preceded by a prolonged period of high growth accompanied by low and stable inflation, the so called 'Great Moderation'. During that period, potential growth estimates were trending upwards and output gaps remained small. However, other imbalances were progressively accumulating, eventually bringing about the worst crisis in decades. Standard potential growth estimates, which consider inflation as the only indicator of macroeconomic imbalances, along with the stability of inflation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
2
21
0
1
Order By: Relevance
“…This closely links our work with the literature on the main factors explaining output fluctuations during the crisis of 2008 (Frankel and Saravelos, 2010;Lane and Milesi-Ferretti, 2011;Cecchetti et al, 2011;Feldkircher, 2014). Our main contribution to these strands of research is that we follow Alberola et al (2013), Borio et al (2013Borio et al ( , 2014 and Bernhofer et al (2014) in employing an empirical model that enables us to decompose output fluctuations into cycle and trend components based on the empirical relationships with various measures of imbalances. The resulting indicators may be interpreted, in an economic sense, as metrics of sustainable (ie not associated with the build-up of imbalances) output and the output gap.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…This closely links our work with the literature on the main factors explaining output fluctuations during the crisis of 2008 (Frankel and Saravelos, 2010;Lane and Milesi-Ferretti, 2011;Cecchetti et al, 2011;Feldkircher, 2014). Our main contribution to these strands of research is that we follow Alberola et al (2013), Borio et al (2013Borio et al ( , 2014 and Bernhofer et al (2014) in employing an empirical model that enables us to decompose output fluctuations into cycle and trend components based on the empirical relationships with various measures of imbalances. The resulting indicators may be interpreted, in an economic sense, as metrics of sustainable (ie not associated with the build-up of imbalances) output and the output gap.…”
Section: Introductionsupporting
confidence: 63%
“…Conveniently, in recent years there has been a significant number of contributions to the literature on such imbalances indicators. In fact, several international organizations have developed various frameworks for the evaluation and early detection of macroeconomic imbalances (see Alberola et al (2013) for a review). We follow these studies (most notably, Alessi and Detken (2011) and Frankel and Saravelos (2010)) in our choice of imbalances indicators, using those that have produced robust results under a variety of specifications of the model.…”
Section: Datamentioning
confidence: 99%
“…As pointed out before, one reason for this may be the breakdown of the Phillips curve relationship during the last years. This has been recently emphasized by, for instance, Koop and Onorante (2012), ECB (2013), Alberola et al (2013), Coibion and Gorodnichenko (2013), and Ormerod et al (2013).…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, the impact of a credit or financial cycle on potential output is documented by Bijapur (2012), Furceri and Mourougane (2012), Borio et al (2013b;a;2014), Benati (2013), Karfakis (2013), Alberola et al (2013). Moreover, Juselius and Juselius (2013) question the functioning of the Phillips curve during balance sheet recessions.…”
mentioning
confidence: 99%
“…However, the crisis in Spain has shown that in that period observed growth was excessive and its nature pernicious for the stability of the system. This paper applies a new methodology to obtain estimates of sustainable growth rates for Spain (see also Alberola et al 2013). The sustainable growth rate is defined as the output growth that does not widen macroeconomic imbalances, which are identified through a wide set of domestic and external indicators (for alternative definitions, see, for example, Basu and Fernald 2009).…”
Section: Motivationmentioning
confidence: 99%